Pengaruh Skeptisme Profesional, Integritas Dan Beban Kerja Terhadap Penilaian Risiko Kecurangan : (Studi Pada Kantor Akuntan Publik Di Kota Bandung) - Apriwandi Apriwandi; Debbie Christine (Politeknik Ganesha Medan, 2023)
This study aims to analyze the effect of professional skepticism, integrity, and workload on fraud risk assessment. This research was conducted on auditors who work at Public Accounting Firms in the city of Bandung. This study uses primary data by distributing questionnaires to the auditors. In this study, 100 respondents became the research sample. Sampling method using purposive sampling technique. This study uses a descriptive method with a survey approach where the respondents who are the sample are auditors who work in several public accounting firms in the city of Bandung. The objects in this study are Professional Skepticism, Integrity, and Workload as independent variables and Fraud Risk Assessment as the dependent variable. The data collection technique was carried out by distributing questionnaires to auditors working at the Public Accounting Firm in the city of Bandung. The results of the simultaneous tests carried out proved that between professional skepticism, integrity and workload, the result was 0.001 on the fraud risk assessment.